Multi-scale characterisation of late-medieval tournois of Frankish Greece provenance. Issue 1 (1st April 2022) - Paladini, G; Acri, G; Caridi, F; Crupi, V; Faenza, P; Majolino, D; Venuti, V
Abstract: An archaeometric investigation on 13 late–medieval tournois was here accomplished through a combined approach involving X–ray fluorescence (XRF) and Raman techniques. The aim of this study was to determine, starting from the evaluation of the elemental and molecular composition, the raw materials employed for the coin's alloy and highlight the differences in the coin's composition according to the location of the original mint and estimated coinage age. The aforementioned aspects not only testify the monetary policy and the political condition of the time, but also would contribute to unambiguously recognize the coin's original treasury, which is at present an ongoing controversy among the scientific/numismatic community. Finally, the identification of specific minerals by means of Raman spectroscopy allowed us to formulate hypothesis about the state of conservation, and to identify new phases resulting from the soil/burial and climatic environmental coin's exposition.